When Resistance Becomes Reproduction: A Critical Action Research Study - Gary Cale (Adult Education Research Conference, 2001)
This paper explores how adult learners in a college composition course resisted pedagogies and teaching strategies designed to critically examine student and teacher assumptions about classism, racism, and sexism as well as other oppressive structures and discourses.